Analisis Modal Kerja Dan Pengelolaan Keuangan Terhadap Pendapatan Pada PT. Nippon Indosari Corpindo TBK - Robyatul Adawiyah; Bangun Putra Prasetya (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine and analyze the influence of working capital and financial management on the case study at PT Nippon Indosari Corpindo Tbk. The methodology used is action research, data sourced from secondary data, the data collection technique for this research uses online sources (available websites), printed sources (research reports) regarding financial reports for 2018 - 2024. The analysis used in this research is regression multiple linear and requires the SPSS version 26 program to process the data. Based on research data testing, the results obtained: working capital has a positive and significant effect on the financial income of PT Nippon Indosari Corpindo Tbk in 2018 - 2024. Likewise, financial management has a positive and significant effect on the financial income of PT Nippon Indosari Corpindo Tbk in 2018 - 2024. Working capital and financial management simultaneously have a positive and significant effect on the financial income of PT Nippon Indosari Corpindo Tbk in 2018 - 2024. It is hoped that the results of this research can provide input for companies, namely as reference material for making policies and decisions regarding working capital and financial management.